Empresas familiares: análise de criação de conhecimento no processo sucessório - Brito, Fellipe Campos (Universidade do Vale do Rio dos Sinos, 2019)
Succession in family businesses is a relevant process for business continuity. Succession effectiveness requires organizational and family planning to maintain family leadership skills in the management and ownership of the business. The creation of organizational knowledge is a fundamental element in the exchange of management, since the succession is involved by interactions between the members of the family and the organization. Thus, the objective of this study is to identify how the activities of family business members create relevant knowledge for the organization to achieve a satisfactory succession process. For this, we created four evidence propositions for a generic qualitative research, analyzing eight cases of family businesses, of which six companies are in the transition phase and two in the succession development phase. The results presented that three research propositions, demonstrate congruence with the literature of the theme, demonstrating positive influence to the succession process. The study demonstrates the results of interactions in each succession phase, identifying as interactions of each successor and the similar elements found as a result of interaction in each case. Finally, the study presents cases that perform more knowledge creating activities, and include more interactions with diverse members, performed better at the succession transition stage.
Keywords: Empresas familiares; Sucessão; Criação de conhecimento organizacional; Espiral do conhecimento; Family business; Succession; Creation of organizational knowledge; Knowledge spiral; ACCNPQ::Ciências Sociais Aplicadas::Administração